Integrating Pancasila and Islamic Values in Early Childhood Character Education via the Pancasila Student Profile Project - Hasanah, Fathiyah; Hasanah, Lathipah; Fauziah, Nabila Zahra; Hikmah, Nur; Auriza, Nasywa (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
This study examines the implementation of the Pancasila Student Profile Strengthening Project (P5) in early childhood education as a holistic strategy for character development from an early age, using a literature study with a qualitative descriptive approach. The findings reveal that early childhood is a golden period for establishing the foundations of character, during which children learn through play, exploration, and imitation. The six dimensions of P5—faith and piety to God Almighty, independence, cooperation, global diversity, critical thinking, and creativity—align with the developmental needs of young children and harmoniously integrate with the spiritual values instilled in early childhood learning activities. The integration of thematic projects such as “I Love the Earth” and “My Imagination” not only cultivates responsibility, empathy, and independence in contextual ways but also provides space for simple faith-based practices such as praying before learning, expressing gratitude for God’s creation, sharing with peers, and helping one another. Through meaningful projects that combine direct experience, reflection, and social interaction, Pancasila values become internalized alongside values of faith and devotion, creating learning experiences that are more humanistic, civilized, and aligned with children’s moral development. Thus, integrating P5 into early childhood education contributes theoretically to strengthening character education models grounded in national and religious values, while also offering a practical strategy for nurturing Indonesian learners who are faithful, virtuous, and capable of living harmoniously within diversity.